The design, properties and performance of shape optimized masonry blocks - Luísa Costa Sousa (2015)
The choice for a certain masonry unit depends mainly on its functional performance. The new European Directives regulations require different solutions challenging manufacturers to develop optimized systems. In particular, in south European countries where the mild winter climate justifies the use of high-thermal-performance masonry walls, the search for optimized masonry units and the design of single-leaf masonry external walls is a challenge. In this chapter, the basic requirements for enclosure walls used in the building façades are analysed. A review of innovative masonry blocks developed in recent years is presented. An example of an optimized lightweight concrete masonry unit, for single leaf enclosure walls with no external insulation, developed within a collaborative project with MAXIT group, is illustrated. The iterative problem of finding the optimal geometry and topology, namely position, size and spacing of the holes within the block that minimizes the wall thermal transmittance, is supported by a genetic algorithm constrained by the characteristics and construction practices of masonry materials. Numerical simulations and laboratory tests of two new wall solutions currently under development at the University of Porto are reported. Finally, future trends for the development of masonry systems are also introduced.